A Logic‐Based Diagnostic and Therapeutic Hydrogel with Multistimuli Responsiveness to Orchestrate Diabetic Bone Regeneration. Issue 11 (3rd February 2022) - Li, Dize; Chen, Kaiwen; Tang, Han; Hu, Shanshan; Xin, Liangjing; Jing, Xuan; He, Qingqing; Wang, Si; Song, Jinlin; Mei, Li; Cannon, Richard D.; Ji, Ping; et al.
Abstract: The regeneration of diabetic bone defects remains challenging as the innate healing process is impaired by glucose fluctuation, reactive oxygen species (ROS), and overexpression of proteinases (such as matrix metalloproteinases, MMPs). A "diagnostic" and therapeutic dual‐logic‐based hydrogel for diabetic bone regeneration is therefore developed through the design of a double‐network hydrogel consisting of phenylboronic‐acid‐crosslinked poly(vinyl alcohol) and gelatin colloids. It exhibits a "diagnostic" logic to interpret pathological cues (glucose fluctuation, ROS, MMPs) and determines when to release drug in a diabetic microenvironment and a therapeutic logic to program different cargo release to match immune‐osteo cascade for better tissue regeneration. The hydrogel is also shown to be mechanically adaptable to the local complexity at the bone defect. Furthermore, the underlying therapeutic mechanism is elucidated, whereby the logic‐based cargo release enables the regulation of macrophage polarization by remodeling the mitochondria‐related antioxidative system, resulting in enhanced osteogenesis in diabetic bone defects. This study provides critical insight into the design and biological mechanism of dual‐logic‐based tissue‐engineering strategies for diabetic bone regeneration. Abstract : A "diagnostic" and therapeutic dual logic‐based hydrogel for diabetic bone regeneration is developed through the design of a double‐network hydrogel responsive to diabetic microenvironmental cues combined with the controlled delivery of anti‐inflammatory and osteogenic protein drugs. The logic‐based drug release enables the regulation of macrophage polarization by remodeling the mitochondria‐related antioxidative system, resulting in enhanced osteogenesis in diabetic bone defects.